Role Environmental Performance on Effect Financial Performance to Carbon Emission Disclosure - Rahmawati, Rahmawati; Setiawan, Doddy; Aryani, Y. Anni; Kiswanto, Kiswanto (International Journal of Energy Economics and Policy, 2024)
Disclosure of carbon emissions has become a global issue amidst the increasing world climate. This issue becomes a tranding that can affect the company's performance supported by the company's environmental performance. This study aims to examine the role of environmental performance in the influence between the company's financial performance on the disclosure of carbon emissions. This research was conducted on Basic Industry and Chemical companies listed on the Indonesia Stock Exchange. The unit of analysis used in this study was 150 observation units. Data analysis uses multiple regression analysis. The results of the analysis show that first: financial performance consisting of liquidity, profitability, leverage, and sales growth has a direct effect on the disclosure of carbon emissions. However, the return on equity ratio has no effect on the disclosure of carbon emissions. Second, the results show that the presence of environmental performance can not maximally encourage the disclosure of carbon emissions. Where the company can improve environmental performance if the company has better financial performance. This is indicated by the value of the direct effect of environmental performance has no effect on the disclosure of carbon emissions. However, this research is limited to basic and chemical companies, so future research can expand to companies that have a direct impact on the environment.